EVALUASI PERFOMANSI PENAMBAHAN GUIDE VANE PADA PENAMPANG CIRCULAR MITER BEND 300 DENGAN STUDI NUMERIK ( STUDI KASUS REYNOLDS NUMBER ReDh 4,744 107 ) - Achjab, Firmansyah; Nugroho, Setyo; l Ulum, Achmad Bahrul (Proceeding SENDI_U, 2015)
Miter bending or curved pipe on the canal of penstock in hydropower has a pressure loss (pressure drop). Thishappens because of the curved shape of the miter bending that causes pressure on the outer wall (outter) biggerand blocking off the pace of the fluid. The value of the pressure loss is affected by the angle of the elbow as wellas a large radius of curvature, which causes secondary flow (secondary flow) resulting in large pressure loss sothat required an effort to minimize this pressure loss. Experiment model is miter bending 300 based on the finalbook drawing hydropower. Research numerically using ANSYS 14.5 with ReDh 4.744 reynolds number 107, themeasured variable is the static pressure and streamlined speed.